The Role of Nurses in Rehabilitation Services: A Holistic Approach to Enhancing Recovery and Promoting Independence - Aeyed Mohammed Aldosari Mansour Abdullah M Aldosari, Barrak Abdullah M Aldosary, Sultan Mohamed M Aldosari; Abdulaziz Muhammad Hamad, Mohammed Mansour M Aldossari, Taghreed Awad Alotaibi, Horaya Saleh Al Aradi (Journal of International Crisis and Risk Communication Research, 2024)
Rehabilitation services are a cornerstone of modern healthcare, aiming to restore functional abilities, improve quality of life, and support the reintegration of individuals with injuries, disabilities, or chronic conditions. Nurses play a pivotal role in these multidisciplinary services, contributing through direct patient care, education, and psychosocial support. This review highlights the multifaceted roles of nurses across different stages of acute, post-acute, and community-based rehabilitation, emphasizing their responsibilities in stabilizing vital functions, enhancing mobility, and promoting long-term self-management. The integration of advanced technologies, including artificial intelligence, wearable devices, telemedicine, and virtual reality, has enhanced nurses’ ability to deliver personalized, effective, and impactful care. Holistic nursing practices address the physical, emotional, and social dimensions of recovery, ensuring patient-centered outcomes.